Chemical constituents of fruits of Khaya senegalensis A. Juss growing in Vietnam - Hien, Vu Thi; Hoang, Vu Dinh (Vietnam Journal of Chemistry, 2016)
Four limonoids, seneganolide (1), khayanone (2), khayanolide B (3), 6-acetoxy-methyl angolensate (4), and two flavonoids, (-)-epicatechin (5) and quercitrin (6), were isolated from the ethyl acetate extract of fruits of Khaya senegalensis A. Juss. Their structures were elucidated by MS and NMR spectroscopic methods as well as comparison with literature data.